Triggers and Consequences of Awe in Online Brand Community. (May 2022) - Zhao, Jianbin; Li, Zheng; Xiong, Guobao
As a common experience-based emotion, awe can easily arise within consumers who are immersed in an online brand community. On the basis of the awe prototype theory, this paper developed a research model involving community management authority, professionalism of opinion leaders, participation time, awe, and customer engagement at the organizational and individual levels of an online brand community. The study then targeted a mobile online brand community, obtaining 409 valid data points using a questionnaire survey platform (wjx.cn). The data were analyzed using a structural equation model, revealing that the management authority and the professionalism of opinion leaders positively affect community members' awe, and this awe positively affects community engagement behaviors. Community members' participation time negatively moderates the influence of management authority on awe; namely, longer participation time weakens such influence. In addition, community members' participation time lowers the effect of opinion leaders' professionalism on their awe, though not significantly. This research advances the study of online communities while also providing practical insights to managers and opinion leaders.